2022
DOI: 10.1016/j.jhepr.2021.100409
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum miR-193a-5p during non-alcoholic fatty liver disease progression: Diagnostic and mechanistic relevance

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In addition to imaging biomarkers, the NIS4 circulating biomarker panel has also been developed to specifically target "at risk" NASH. 110 This panel incorporates a circulating micro-RNA (miR34a), which has been independently validated to associate with NASH and fibrosis, 111 combined with indirect biomarkers of inflammation and glucose tolerance (alpha-2 macroglobulin, YKL-40, and glycated haemoglobin), achieving an AUROC of 0.80 (0.77-0.84) and outperforming simple panels such as FIB-4. 110…”
Section: Surveillance After Hcv Eradicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to imaging biomarkers, the NIS4 circulating biomarker panel has also been developed to specifically target "at risk" NASH. 110 This panel incorporates a circulating micro-RNA (miR34a), which has been independently validated to associate with NASH and fibrosis, 111 combined with indirect biomarkers of inflammation and glucose tolerance (alpha-2 macroglobulin, YKL-40, and glycated haemoglobin), achieving an AUROC of 0.80 (0.77-0.84) and outperforming simple panels such as FIB-4. 110…”
Section: Surveillance After Hcv Eradicationmentioning
confidence: 99%
“…167 Analysis of circulating micro-RNA biomarkers has also proved fruitful with at least one, miR34a, now being incorporated into a commercially available panel. 110,111 Complementing these studies by adopting a proteomics-driven approach, aptamer-based profiling of a US cohort identified 8 circulating proteins including ADAMTSL2 (A disintegrin and metalloproteinase with thrombospondin motifs like 2) as potentially tractable biomarkers of advanced hepatic fibrosis in NAFLD. 63 Metabolomic profiling has similarly proved highly tractable, especially in NAFLD where studies have supported identification of dynamic biomarkers that reflect changes in disease severity, indicating steatohepatitis activity and fibrosis stage.…”
Section: Future Personalised Medicine and Noninvasive Testsmentioning
confidence: 99%
“…In addition to this, there is growing evidence that NAFLD causes alterations in the production of several molecular coordinators that may be detrimental to bone health, such as overproduction of TNF-a ( 32 ) and deficiencies in vitamin D ( 33 ), osteopontin ( 34 ) and osteoprotegerin ( 35 ). Moreover, circulating molecules may have different effects on bone metabolism by affecting early childhood obesity ( 36 ) or the progression of NAFLD ( 37 ). However, it is reasonable to believe that increased body weight is a prevalent trait of people with NAFLD ( 38 ), may help to prevent bone loss by increasing mechanical loads and improving cortical bone growth.…”
Section: Discussionmentioning
confidence: 99%
“…They found that ADC was closely associated with expression of miR-200b, miR-21, and miR-29, and the accuracy of ADC combined with miR-200b to distinguish early and late liver fibrosis was 80.2%[ 68 ]. In a discovery cohort of 183 patients with non-alcoholic fatty liver disease, scientists identified that plasma miR-193a-5p was consistently maintained at a high level and was closely associated with grade of fibrosis, which was verified in a cohort of 372 additional cases[ 69 ]. Results from another study confirmed that miR-103a-3p and miR-425-5p were stably expressed in exosomes of serum derived from mice and humans infected with schistosomiasis[ 70 ].…”
Section: Potential Application Of Ncrnas In the Diagnosis Of Liver Fi...mentioning
confidence: 99%